Significant shifts in coastal zooplankton populations through the 2015/16 Tasman Sea marine heatwave. (5th April 2020) - Evans, R.; Lea, M.-A.; Hindell, M.A.; Swadling, K.M.
Abstract: The waters east of Tasmania, Australia, are warming at a rate 3–4 times the global average, largely as a result of the increasing duration and frequency of the southward penetration of the East Australia Current (EAC). In 2015/16, the southward movement of this sub-tropical current caused a severe marine heatwave (MHW) event. The effects of this event on the abundance and structure of the zooplankton community of south-east Tasmania are examined between November 2015 and January 2018. Generalized additive models indicated temperature to be significantly correlated with total zooplankton abundance (R 2  = 0.6, p < 0.001). When modelled separately, species groups that are highly associated with the EAC, including bryozoan larvae (R 2  = 0.2), echinoderm larvae (R 2  = 0.6) and gelatinous zooplankton such as thaliaceans (R 2  = 0.3), exhibited significant positive relationship with temperature (p < 0.001). The most abundant groups in samples; copepods (R 2  = 0.6), appendicularians (R 2  = 0.5) and cladocerans (R 2  = 0.2), all exhibited negative relationships (p < 0.001; p < 0.001; p < 0.01, respectively). The abundances of cold-water and warm-water species of copepods were also analysed in relation to temperature. Sub-tropical species which are indicative of the East Australia Current, such as copepods from the Family Corycaeidae, and the calanoids Temora turbinata and Acartia danae, were present when temperatures exceeded ~17 °C, with a concurrent drop in the abundance of cold-water species. The east-coast of Tasmania is a region of rapid oceanographic change, and we have linked these changes with shifts in zooplankton population structure. Long-term studies from other regions that have also experienced marine heatwaves indicate these changes may have cascading implications for higher trophic levels. Gelatinous zooplankton and other zooplankton taxa not previously observed have now been documented in local predator diets. During warm periods, these species may represent an important alternative energy pathway. Highlights: Warming is occurring off south-east Tasmania due to an increase in the intensity of the East Australia Current. These changes are causing a shift in the abundance and composition of the zooplankton community. Groups that are highly associated with the EAC exhibit significant positive relationships with temperature. Warmer SSTs lead to an increase in sub-tropical species of copepods, while the abundance of cold-water species decreases.